A new capital regulation for large financial institutions - Oliver Hart; Luigi Zingales (Fondazione Eni Enrico Mattei (FEEM), 2009)
We design a new, implementable capital requirement for large financial institutions (LFIs) that are too big to fail. Our mechanism mimics the operation of margin accounts. To ensure that LFIs do not default on either their deposits or their derivative contracts, we require that they maintain an equity cushion sufficiently great that their own credit default swap price stays below a threshold level, and a cushion of long term bonds sufficiently large that, even if the equity is wiped out, the systemically relevant obligations are safe. If the CDS price goes above the threshold, the LFI regulator forces the LFI to issue equity until the CDS price moves back down. If this does not happen within a predetermined period of time, the regulator intervenes. We show that this mechanism ensures that LFIs are always solvent, while preserving some of the disciplinary effects of debt.
Keywords: G21; G28; 330; Banks; Capital Requirement; Too Big to Fail